2018
DOI: 10.1111/cns.13064
|View full text |Cite
|
Sign up to set email alerts
|

Loss of GINS2 inhibits cell proliferation and tumorigenesis in human gliomas

Abstract: Summary Aims In this study, we examined the expression of GINS2 in glioma and determined its role in glioma development. Methods The protein expression of GINS2 was assessed in 120 human glioma samples via immunohistochemistry. Then, we suppressed the expression of GINS2 in glioma cell strains U87 and U251 using a short hairpin RNA lentiviral vector. In addition, RNA sequencing and bioinformatics analysis were performed on glioma cells before and after GINS2 knockdown. Subsequent co‐immunoprecipitation and wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…For example, Liu et al [37] found that lung cancer tissues over-expressed GIN2, which was connected to lung cancer metastasis. Recent years, some studies have found that GINS2 is a novel prognostic biomarker and promoted tumor progression in early-stage cervical cancer [38]; GINS2 is closely related to the occurrence and development of glioma, and may become a prognostic marker for glioma patients [39]; GINS2 is markedly expressed in EOC tissues and cell lines, stable GINS2 knockdown in SKOV-3 cells could significantly inhibit cell proliferation and induce cell cycle arrest and cell apoptosis [40]. In current study, survival analysis of the hub genes related to target genes of miR-182 showed that GINS2 was highly associated with poor prognosis of patients with OC.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Liu et al [37] found that lung cancer tissues over-expressed GIN2, which was connected to lung cancer metastasis. Recent years, some studies have found that GINS2 is a novel prognostic biomarker and promoted tumor progression in early-stage cervical cancer [38]; GINS2 is closely related to the occurrence and development of glioma, and may become a prognostic marker for glioma patients [39]; GINS2 is markedly expressed in EOC tissues and cell lines, stable GINS2 knockdown in SKOV-3 cells could significantly inhibit cell proliferation and induce cell cycle arrest and cell apoptosis [40]. In current study, survival analysis of the hub genes related to target genes of miR-182 showed that GINS2 was highly associated with poor prognosis of patients with OC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study showed that some genes were significantly related to prognosis and may be potential biomarkers for gliomas, such as NUSAP1 ( 56 ), GINS2 ( 57 ), TRIM21 ( 58 ), IL-6 ( 59 ) and LATS1 ( 60 ). However, the potential therapeutic targets in the treatment of gliomas are still elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…A high GINS2 transcript level predicts poor prognosis and correlates with high histological grade and endocrine therapy resistance through mammary cancer stem cells in breast cancer patients, 30 and GINS2 regulates matrix metallopeptidase 9 expression and cancer stem cell property in human triple negative breast cancer. 31 GINS2 promotes cell proliferation and inhibits cell apoptosis in thyroid cancer by regulating Cbp/p300-interacting transactivator 2 and lysyl oxidase like 2; 32 knockdown of GINS2 inhibits cell proliferation and tumorigenesis in human gliomas; 33 GINS2 promotes EMT in pancreatic cancer via specifically stimulating extracellular signal-regulated kinase 1/2/mitogen-activated protein kinase signaling. 34 In the cervical cancer, Chen et al, found that GINS2 was up-regulated in the SiHa cells and cervical cancer tissues.…”
Section: Discussionmentioning
confidence: 99%